Characteristics of The Crime of Genocide in An International Criminal Law Perspective - Simanjuntak, Tuti Gusmawati; Harahap, Lili Rahmayana; Sembiring, Ahmad Mulia; Bahraini (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
The crime of genocide, characterized by the systematic extermination of an ethnic or cultural group, is intrinsically linked to the persecution of a political entity, which often complicates the identification of the affected group and poses significant challenges to international relations. Recognized as an exceptional crime in the realm of international criminal law, genocide has been unequivocally condemned and prohibited, as articulated in important legal frameworks such as the 1948 Genocide Convention, the statutes of the International Criminal Tribunals for the Former Yugoslavia (ICTY) and Rwanda (ICTR), and the 1998 Rome Statute. This study utilizes a normative legal research methodology, which draws on primary legal materials, including relevant regulations and documents, to conduct a thorough qualitative analysis. To effectively answer the research questions, we used a combination of conceptual, statutory and case law approaches, each of which contributed to a comprehensive understanding of the topic at hand. The results state that the nature of genocide is summarized in several tragic acts: the intentional deprivation of life of members of a particular group, inflicting severe physical or psychological suffering on them, and intentionally creating conditions that lead to the physical extermination of that group, either in whole or in part. In addition, genocide includes the adoption of measures designed to prevent births within the group and the forcible removal of children from their families for integration into other groups.